Analysis of Photocatalytic Degradation of Phenol by Zinc Oxide Using Response Surface Methodology - Seloglu, Meliha; Orhan, Ramazan; Selen, Veyis; Dursun, Gulbeyi (Wiley-V C H Verlag Gmbh, 2024)
In this study, the photocatalytic degradation of phenol, which is commonly found in industrial wastewater at high rates, was investigated using a zinc oxide (ZnO) catalyst. It is thought that our findings will contribute to the removal of phenol in industrial wastewater. The experimental study was conducted in a batch-type air-fed cylindrical photocatalytic reactor, and a central composite design (CCD) was chosen and analyzed using response surface methodology (RSM). The study aimed to explore the effects of initial phenol concentration, catalyst concentration, airflow rate, and degradation time on the photocatalytic degradation of phenol and the removal efficiency of total organic carbon (TOC). A quadratic regression model was developed to establish the relationship between phenol degradation, TOC removal effectiveness, and the four factors mentioned. The validity of the model was assessed through an analysis of variance (ANOVA). A good agreement was observed between the model results and the experimental data. As a result of the experiments carried out under optimized conditions, the degradation percentage of phenol was found to be 77.15 %, and the degradation percentage of TOC was 59.87 %. Additionally, pseudo-first-order kinetics were used in the photocatalytic degradation of phenol. Phenol and phenolic compounds pose a serious threat to the ecosystem, human health, and water resources. Photocatalytic degradation is the most suitable technique for removing organic pollutants from wastewater, and ZnO is an effective photocatalyst. This study evaluated both the photocatalytic degradation of phenol and the measurement of TOC using a ZnO photocatalyst, demonstrating the feasibility of employing RSM.image
Keywords: ZnO; Photocatalytic degradation; Response surface methodology; Phenol; Degradation mechanism